Forrest Gump - Hanks, Tom.; Wright, Robin, 1966-; Sinise, Gary.; Williamson, Mykelti; Field, Sally; Zemeckis, Robert, 1952-; Roth, Eric.; Finerman, Wendy; Tisch, Steve; Starkey, Steve; Silvestri, Alan.; Groom, Winston, 1944-; et al. (Hollywood, CA : Paramount Pictures, 2001)
The story follows the life of low I.Q. Forrest Gump (Tom Hanks) and his meeting with the love of his life Jenny. The film chronicles his accidental experiences with some of the most important people and events in America from the late 1950's through the 1970's including a meeting with Elvis Presley, JFK, Lyndon Johnson, Richard Nixon, fighting in Vietnam, etc. The problem is, he doesn't realize the significance of his actions. Forrest comes to embody a generation.
DVD, Dolby digital surround.
Dialogue in English or French; close-captioned.
Originally produced as a motion picture in 1994.
Based on the novel by Winston Groom.
Director of photography, Don Burgess ; editor, Arthur Schmidt ; music, Alan Silvestri ; production designer, Rick Carter ; costume designer, Joanna Johnston ; produced by Wendy Finerman, Steve Tisch, Steve Starkey ; screenplay by Eric Roth ; directed by Robert Zemeckis.
Tom Hanks, Robin Wright, Gary Sinise, Mykelti Williamson, Sally Field.
Keywords: People with mental disabilities -- United States -- Drama; Love -- Drama; Feature films; Video recordings for the hearing impaired